Assessment of microbial diversity and antimicrobial resistance in raw camel milk: Genomic and phenotypic analysis of Kharai and Kutchi breeds of Gujarat, India - Hetvi J. Adhyaru; Devangi B. Mangroliya; Jayesh H. Kabariya; Vimal M. Ramani (The Microbe)
Camel milk is increasingly recognized for its nutritional and therapeutic properties, especially in regions like India, which ranks seventh globally in camel population. This study focused on analyzing the microbiome and antimicrobial resistome in raw camel milk from two unique breeds, Kharai and Kutchi, found in Gujarat's Kutch district. Both breeds exhibit unique microbial compositions, with the Kharai breed having a more diverse bacterial community. Through phenotypic antimicrobial resistance analysis using the disc diffusion method, a significant number of multidrug-resistant (MDR) and extensively drug-resistant (XDR) bacterial isolates were identified. The genotypic analysis, performed via nanopore metagenomic sequencing, revealed the presence of various antimicrobial resistance genes (ARGs). In the Kharai breed 58 ARGs were detected, majority of them conferring resistance to fluoroquinolones, tetracycline, macrolides, and colistin. In contrast, 13 ARGs were detected in the Kutchi breed, with a focus on resistance to fluoroquinolones and spectinomycin. In addition to pathogenic bacteria, beneficial lactic acid bacteria such as Lactobacillus and Enterococcus were identified in the Kharai breed milk, contributing to its probiotic potential. However, the diversity of pathogenic bacteria was very low as compared to bovine milk, including Acinetobacter, Staphylococcus, Klebsiella, and Salmonella, in both breeds. Importantly, the study found that camel milk harboured fewer ARGs related to last-resort antibiotics, such as β-lactams, compared to bovine milk. This suggests that camel milk poses a lower risk compared to other raw milk sources with respect to spread of antimicrobial resistance (AMR). The findings underline the need for monitoring camel milk to safeguard public health. This comprehensive assessment of both genotypic and phenotypic AMR profiles in raw camel milk provides crucial insights into its microbial diversity and spread of antimicrobial resistance.